Direct and specific analysis of nitrite and nitrate in biological and non-biological samples by capillary ion analysis for the rapid identification of fatal intoxications with sodium nitrite. (August 2021) - Taus, Francesco; Pigaiani, Nicola; Bortolotti, Federica; Mazzoleni, Guido; Brevi, Michele; Tagliaro, Franco; Gottardo, Rossella
Highlights: CE-UV has been applied to the quantification of nitrite and nitrate in post-mortem specimen. The method was applied to the quantitative determination of these ions in authentic forensic cases. This is the first application of CE to the determination of nitrite/nitrate in fatalities. Abstract: In recent years, a significant increase of reports about suicidal cases due to intentional sodium nitrite intake has been described. In the forensic pathology context, the strategy to approach intoxication cases by sodium nitrite, without any preliminary information or hint, is not straightforward. Indeed, in a number of cases the lack of crime scene data and/or specific pathological signs makes difficult the identification of nitrite poisoning. Moreover, the analytical determination of nitrite in blood is challenging, due to its rapid oxidization to nitrate by hemoglobin. Although several methods have been proposed for the clinical analysis of nitrate and/or nitrite in biological samples, none of these is specifically focused on the determination of these ions in cadaveric samples. Consequently, the diagnosis of nitrite fatal intoxication is still based on methemoglobin analysis. The present paper reports the optimization and validation of an analytical method of capillary ion analysis (CIA) with UV detection, for the determination of nitrite and nitrate in biological fluids and its application to two authentic cases of death by nitrite intake. The analyses were carried out in a bare fused-silica capillary (75 µm inner diameter) using 100 mM sodium tetraborate (pH 9.24) as background electrolyte and applying a voltage of − 15 kV between the capillary ends. The detection was obtained by direct UV absorption recorded at 214 nm wavelength. Bromide was used as the internal standard. Linearity was established in the range of 0.25–5 mmol/L). Reproducibility (intraday and day-to-day) was characterized by relative standard deviations (RSDs) 14.7% for peak areas. The method was applied to the determination of nitrite and nitrate in two real forensic cases, where high concentrations of nitrate were found in cadaveric blood samples (6.5 and 4.4 mmol/L, respectively). Nitrite was found only in trace amounts, due to the instability of this ion in cadaveric blood where it is oxidized to nitrate. The present method represents a new tool for the direct and rapid determination of nitrite and nitrate in cases of forensic interest, and thus offers a diagnostic tool more sensitive and precise than the need methemoglobin analysis.